O etanol e a gasolina são substitutos perfeitos ? - Guimarães, Ângela (2008)
The relative domestic prices behavior for fuels (relationship among price of ethanol and gasoline) was analyzed accord to panel monthly ones on 27 Brazilian units during the period from July 2001to February 2008. They released by ANP and through Box-Jenkins methodology. It was empirically verified that relative prices seem to follow a first-order autoregressive process, AR(1), with an average ratio equal marginal utility of ethanol (sugarcane) and gasoline (fossil fuel) liters, which is equal technical coefficient of 70 %. This result suggests that owners of dual-fuel ehicle technology in the face of consumer arbitrage became the natural official regulator of this market such as short as long term.